Building and sustaining the defense simulation training workforce. (April 2021) - Blackmore, Karen Louise; Allitt, Evan William Henry
The delivery of simulation training capability across the Australian Defence Force (ADF) requires a highly skilled workforce. Evolving training requirements, enabled by advances in computing power, network systems, display and peripheral technologies, and software environments, place increasing demands on the size of the workforce and the technical skills they are required to possess. In this research, we analyze existing simulation role frameworks and the various position descriptions and qualification requirements associated with these roles. To further explore the unique skillsets that translate to success in simulation roles, we also conduct a case study of a large external contract simulation workforce supplier, Cubic Defence Australia. Our findings highlight the complexity of the defense simulation workforce, including the lack of standardized position descriptions, competency frameworks, education and training pathways, and career progression options. Further complicating this is the importance of prior ADF service experience to the delivery of simulation systems that meet active training requirements, and the relationship between this service experience and career progression. From this analysis, recommendations for addressing the issues are made, including a call for a targeted and deliberate, multi-industry federal response to broaden the pool of candidates looking for careers in simulation.